Self-Buffering Organocatalysis Tailoring Alternating Polyester - Li, Heng; Zhao, Junpeng; Zhang, Guangzhao (ACS macro letters, 2017)
A major success has been made on organocatalytic ring-opening alternating copolymerization (ROAP) of phthalic anhydride and ethylene oxide (EO) by use of a simple phosphazene base (t-BuP1). Polyesters with perfectly alternating sequence distribution, controlled molar masses, and low dispersities (Đ M < 1.1) are obtained. The ROAP exhibited a distinct living nature so that block, nonlinear, end-functional structures and postpolymerization modification of the alternating polyesters are readily achieved. Solvent, excess EO, and catalyst can be effortlessly recovered and reused. The ideally suitable basicity of t-BuP1 is considered crucial for the high selectivity and neatness of the ROAP, which engenders a self-buffering mechanism rendering the carboxy and hydroxy terminals appropriately active to allow chain growth in an strictly alternating manner and complete avoidance of side reactions (epoxide self-propagation, transesterification) even at full conversion of the anhydride.